COMPARISON OF INDONESIAN AND SINGAPORE PATENT LAW (Analytical Study in the field of Science and Technology) - Ridwan, Ali; Iskandar, Iskandar (Program Studi Hukum Tata Negara, 2024)
: Intellectual Property Rights are a person's rights to their inventions in the form of works of art, names and symbols used by someone in the world of commerce. A person's work or creation in the field of art, symbols and names has a connection with the world of commerce, so a person's findings or creations, which are considered intellectual property, must be protected so that they are not misused. The rules regarding Intellectual Property Rights are written in the WTO agreement, namely the TRIPs Agreement, which has been in effect since 1995. Indonesia and Singapore are the two countries that participated in ratifying these rules. In Indonesia, patents are regulated in Law No. 13 of 2016 concerning Patents. Meanwhile, the rules regarding patent protection in Singapore are regulated by the Patents Act, which is based on the British Patent Act 1977. Singapore patents are protected internationally under the Patent Cooperation Treaty (PCT). In defining patent law, Indonesia and Singapore have similar characteristics, this is because they both have similarities and significant differences because they both originate from TRIPs. As for the registration system and everything that contains systematics and procedures related to patent law, both have similarities. Indonesia and Singapore also have the same provisions regarding inventors having exclusive economic and moral rights. Keywords: IPR, Patent Law, TRIPs Agreement.